Differences between Mycobacterium chimaera and tuberculosis Using Ocular Multimodal Imaging: A Systematic Review - Sandrine Anne Zweifel (MDPI AG, 2021)
Due to their non-specific diagnostic patterns of ocular infection, differential diagnosis between Mycobacterium (M.) chimaera and tuberculosis can be challenging. In both disorders, ocular manifestation can be the first sign of a systemic infection, and a delayed diagnosis might reduce the response to treatment leading to negative outcomes. Thus, it becomes imperative to distinguish chorioretinal lesions associated with M. chimaera, from lesions due to M. tuberculosis and other infectious disorders. To date, multimodal non-invasive imaging modalities that include ultra-wide field fundus photography, fluorescein and indocyanine green angiography, optical coherence tomography and optical coherence tomography angiography, facilitate in vivo examination of retinal and choroidal tissues, enabling early diagnosis, monitoring treatment response, and relapse detection. This approach is crucial to differentiate between active and inactive ocular disease, and guides clinicians in their decisional-tree during the patients’ follow-up. In this review, we summarized and compared the available literature on multimodal imaging data of M. chimaera infection and tuberculosis, emphasizing similarities and differences in imaging patterns between these two entities and highlighting the relevance of multimodal imaging in the management of the infections.